Notes on araceae of Kuala Koh, Kelantan, Peninsular Malaysia - Zulhazman Hamzah; Mashhor Mansor; P.C.Boyce (2011)
A total of 32 speciees from 11 genera of aroids were collected from Kuala Koh, Gua Musang, Kelantan. This represents about 23% out of an estimated 140 species and 39% of the 28 genera of aroids reported for Peninsular Malaysia. These include 24 species that are new records for Kelantan, including the recently described Homalomena kualakohensis Zulhazman, Mashhor & P.C. Boyce, and the very rare Rhaphidophora corneri P.C.Boyce, refound after 75 years.